2012
DOI: 10.4315/0362-028x.jfp-12-217
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-Life Extension and Sanitation of Fresh Pork Loin by E-Beam Treatment

Abstract: The usefulness of electron beam (E-beam) irradiation to increase the shelf life of whole fresh pork loin stored at 4°C has been studied. The shelf life was extended from 5 to 11 and 20 days after the application of 1 and 2 kGy, respectively. If a temperature abuse situation were to occur during product distribution (e.g., increase to 8°C), the shelf life would be extended from 3 to 8 and 15 days, respectively, after application of the same doses. When considering Listeria monocytogenes from a public health po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
(87 reference statements)
4
12
1
1
Order By: Relevance
“…The effect of E-beam treatment (1 and 2 kGy) on the former parameters was negligible, except for WHC (Table 1). These results, excluding the latter feature, are in total agreement with previous data obtained for E-beam treated fresh pork loin [30]. The effect of radiation on the pH has been of concern of other authors.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The effect of E-beam treatment (1 and 2 kGy) on the former parameters was negligible, except for WHC (Table 1). These results, excluding the latter feature, are in total agreement with previous data obtained for E-beam treated fresh pork loin [30]. The effect of radiation on the pH has been of concern of other authors.…”
Section: Resultssupporting
confidence: 92%
“…The slices showed a significant increase of the WHC ( P < 0.05) just after the E-beam treatment. This result is completely opposite to what occurred in fresh loin, in which a decrease of the WHC was found [30]. Other authors [51, 53] have also reported a decrease in WHC, an increase in soluble protein, and exudates loss in irradiated pork longissimus dorsi muscle.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…전자선을 식품에 조사할 경우에 식품에서 맛이나 영양에 큰 영향을 미치지 않고 미생물의 세포수를 크게 감소시키거나 또는 미생물을 제거하여서 저장성을 증가시켰다는 것이 보고 되었다 [2,6,7,10,11,16]. 또한 식물 종자의 살균에 전자선이 효과적이었다는 보고도 있다 [15] .…”
unclassified